SYNONYMY AS A LINGUISTIC PHENOMENON IN THE PHRASEOLOGICAL UNITS OF THE ENGLISH AND UZBEK LANGUAGES (International journal of artificial intelligence, 2025)
This research focuses on the linguistic phenomenon of phraseological synonymy in Uzbek and English languages. The study analyzes the semantic and stylistic features of synonymous phraseological units, the factors behind their formation, and their frequency and usage in speech. It also distinguishes between synonymy and variation in phraseology and presents comparative examples from both languages. The findings highlight the role of phraseological synonyms in enriching speech and deepening the understanding of subtle semantic and stylistic meanings.